ANALISIS RISIKO PEMBELAJARAN DARING MENGGUNAKAN METODE FAILURE MODE EFFECT ANALYSIS - Akhmad Rizal Amrulloh; Winarno . (Institut Pendidikan Tapanuli Selatan, 2021)
Education is a source of progress for a country, with guaranteed education, the quality of a country's human resources can improve properly. Therefore education is important because it is one of the foundations of the country's progress. But with the Covid-19 pandemic, almost all patterns of human life have changed, including the field of education. Through a circular letter from the Ministry of Education and Culture, it is instructed that all learning activities be carried out boldly during this pandemic. At the time of courageous learning, there are often problems experienced by the community. This study aims to determine the risk of daring school learning during the Covid-19 pandemic. It is hoped that the results of this study will become a proposal for consideration by the school. To identify the learning model, the Failure Mode Effect Analysis method was used. The results of this study identify the risk of daring learning problems, which arise because the learning process is not optimal during the current pandemic. In this research, data collection was carried out by sending questionnaires to 20 guardians of students. Based on data collection and processing, the highest Risk Priority Number is 252. This figure is identified by the limited number of devices (Hp, Laptop and Computer) owned.